Leveraging the S-O-R Framework to Determine Tourists' Willingness to Revisit Riau Island - Keni Keni; Nicholas Wilson; Fajri Adrianto; Purnama Dharmawan; Ai Ping Teoh (Jurnal Komunikasi, 2024)
Despite being a popular destination, Riau Island's tourist numbers have declined as of April 2024, and remain lower than those of other Indonesian destinations. Therefore, prompt actions are needed to increase the number of visitors. Therefore, using the stimulus-organism-response (S-O-R) framework, this research delves into the intricate factors that mold individuals' propensity to revisit Riau Island. Employing a survey-centric methodology, an extensive dataset was scrupulously amassed from eligible participants through the deployment of digital questionnaires. Stringent criteria were implemented via purposive sampling, ensuring respondents had frequented Riau Island at least thrice in the preceding two years. The two-month duration of data collection yielded a robust dataset, encompassing a total of 154 responses. The analysis, executed using the Partial Least Squares (PLS) method in SmartPLS 4 software, validates the affirmative impact of both destination quality and destination source credibility on tourist satisfaction and the willingness to revisit. Furthermore, the results disclose that tourist satisfaction functions as a positive mediator in these relationships. This implies that the perceived destination quality and source credibility indirectly contribute to the probability of future visits by positively influencing the overall satisfaction of tourists. These findings not only enrich people’s understanding of the determinants influencing individuals' choices to revisit a destination, but also present valuable implications for enhancing destination management and marketing strategies, ultimately aiming to elevate the overall tourist experience. In essence, this study adds to a refined comprehension of the dynamics underlying repeat visitation behaviors, opening avenues for strategic interventions in the tourism sector.